CULTURAL HERITAGE IN ALGERIA: A CRUCIAL DETERMININANT FOR TOURIST ATTRACTIVENESS AND COMPETITIVENESS? - SOUALAH, Amira; BOUSSOUF, Mouatez Billah; Ariane, Houria (Revista de turism - studii și cercetări în turism, 2021)
Like many countries in the world, Algeria is struggling to find its place in global tourism competitiveness market. this article aims highlight the role of Algeria’s both natural and cultural heritage resources as part of the Maghreb, based on the methodology of ranking countries according to their travel and tourism competitiveness specific to the World Economic Forum. In addition, the study also attempts to point out the influence of other indicators on this competitiveness, and to broach the limitations of this tool -Tourism and Travel Competitiveness Report- in terms of the distribution of indicators and the choice of variables in the tourism competitiveness assessment process.